2019
DOI: 10.21037/jtd.2019.06.50
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of endoscopic ultrasound in esophageal cancer staging

Abstract: Since its advent in the 1980s endoscopic ultrasound (EUS) has played an important role in the diagnosis, staging, and therapeutic management of various gastrointestinal malignancies. EUS has emerged as a vital tool in the evaluation of esophageal cancer as it provides a detailed view of the layers of the esophageal wall and surrounding tissues. This permits determination of tumor invasion depth and local lymph node metastases. It is the most sensitive and specific method available for locoregional staging of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 54 publications
1
30
0
2
Order By: Relevance
“…It can provide detailed images and delicate measurement of the oesophageal layers, but it has the same disadvantages of conventional endoscopy discussed above. Measuring one or more layers of the oesophagus is found useful in many circumstances such as assessment of the response to the chemoradiotherapy in oesophageal cancer, characterisation of the strictures and determining the stage of the malignancy 13‐15 . Furthermore, oesophageal wall thickness measured by endoscopic ultrasonography and wall thickness measurements have previously been related to dysmotility in GERD 16 …”
Section: Discussionmentioning
confidence: 99%
“…It can provide detailed images and delicate measurement of the oesophageal layers, but it has the same disadvantages of conventional endoscopy discussed above. Measuring one or more layers of the oesophagus is found useful in many circumstances such as assessment of the response to the chemoradiotherapy in oesophageal cancer, characterisation of the strictures and determining the stage of the malignancy 13‐15 . Furthermore, oesophageal wall thickness measured by endoscopic ultrasonography and wall thickness measurements have previously been related to dysmotility in GERD 16 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of EC remains challenging but is best approached by a multidisciplinary team (4). With the use of neoadjuvant chemotherapy (NAC) and neoadjuvant chemoradiotherapy (nCRT) in the field of EC, more than half of the patients who received platinum-based neoadjuvant therapy have clinical benefit, which is significantly improved compared with the benefits seen from surgery alone (5)(6)(7).…”
Section: Original Articlementioning
confidence: 99%
“…Endoscopic ultrasonography (EUS) is the best method to determine the extent of local early lesions, but this method fails sometimes because luminal stenosis is not rare in EC patients ( 4 ). Moreover, some studies have shown that the preoperative EUS stage was not consistent with the postoperative pathological stage ( 5 , 6 ). On the other hand, unlike in Western countries, where esophageal adenocarcinoma (EAC) is predominant, approximately 90% of EC is squamous cell carcinoma in China ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 98%